On the sum of an almost abelian Lie algebra and a Lie algebra finite-dimensional over its center - Petravchuk, A. P.; Петравчук, А. П.; Петравчук, А. П. (Institute of Mathematics, NAS of Ukraine, 1999)
We consider a Lie algebraL over an arbitrary field that is decomposable into the sumL=A+B of an almost Abelian subalgebraA and a subalgebraB finite-dimensional over its center. We prove that this algebra is almost solvable, i.e., it contains a solvable ideal of finite codimension. In particular, the sum of the Abelian and almost Abelian Lie algebras is an almost solvable Lie algebra.